Creating Reward-Based Learning Strategies to Stimulate Student's Laziness Level: A Case Study at Buddhist Sunday School - Noning Noning; Widiyanto Widiyanto; Sutiyono Sutiyono; Komang Sutawan; Susanto Susanto; Widi Astuti; Tejo Ismoyo (Universitas Sebelas Maret, 2024)
Reward-based learning strategies on the level of laziness of Buddhist Sunday School students. The problems among Buddhist Sunday School students are that some students are too lazy to come to the monastery, lack motivation and participation in learning activities, and prefer other activities such as playing games and then coming to the monastery. This study uses a quantitative approach with a survey method. The population in this study was 31, which was obtained by collecting data after distributing questionnaires. The study was conducted at the monastery and included respondents from Buddhist Sunday school students. The study's results showed a negative influence between reward-based learning strategies on the level of laziness of Buddhist Sunday School students in 2024, with a t count of -9.285 and a significance value (p) of 0.000 > 0.0. The simple regression analysis calculation results obtained the R Square value as 0.748. It means that reward-based learning strategies affect the laziness of Buddhist Sunday school students by 74.8%, and other factors influence the remaining 25.2%.